The Economic Payoff of Name Americanization - Biavaschi, Costanza; Giulietti, Corrado; Siddique, Zahra (Journal of Labor Economics, 2017)
We provide the first evidence of the magnitude and consequences of the Americanization of migrants’ names in the early twentieth century. We construct a longitudinal data set of naturalization records, tracking migrants and their naming choices over time. We consistently find that migrants who Americanized their names experienced larger occupational upgrading than those who did not. Name Americanization embodies an intention to assimilate among low-skilled migrants and reveals the existence of preferences for American names within the labor market. We conclude that the trade-off between individual identity and labor market success was present then as it is today.